Akçakoca Destinasyonu’nun Tarihî İnsan Ekolojisi: Karadenizin Kıyıcığında Romanı - Hatırnaz, Beyza (Folklor/edebiyat, 2022)
Rıfat Ilgaz is a significant novelist, poet and storyteller. Ilgaz, who is also from Western Balck Sea Region, novelized human and human relations which he observed in cities he was raised and lived, and created panoramas of regions which remained away from attention. Karadenizin Kıyıcığında is a novel about the struggles of how the people of Akçakoca survive, whom are trapped in the triangle of geography, climate, and monarchy. Their struggle not only shapes their lives, lifestyles and priorities but also affects their approach to each other and nature. With its deep characters and plot, the novel presents the relationship networks and lifestyles of country folk in Akçakoca, Anatolia and worldwide wrapped around a love story. In the conclusion part, the subject is evaluated within the framework of the ecological ethics ideas and Darwin’s definitions of human, in terms of the similarities which are seen in the approach to nature and women, and the clear characteristics seen in the interaction with nature. Rıfat Ilgaz, consciously or not, presents proof for the claim that hierarchical structures, which have been the subject of the ecological ethics approaches for many years, shape the approach to nature and to those who are considered as “the other” with his real human profiles and human ecology which are presented in his novel and fictionalized with his observations over the years.